Exploring factors influencing skin incision to the delivery time and their impact on neonatal outcomes among emergency cesarean deliveries indicated for non-reassured fetal heart rate status - Zewdu, Dereje; Tantu, Temesgen; Degemu, Fikretsion; Hawlet, Michael; Dejene, Nitsuh; Asefa, Emebet (Frontiers in Pediatrics, 2023)
The time interval between skin incision and delivery (S-D) is crucial in determining neonatal outcome; however, little is known about the influencing factors and their impact on neonatal outcomes, particularly among emergency cesarean deliveries (ECD) indicated for fetal distress. This study investigated the factors influencing S-D time and their effects on neonatal outcomes among mothers who underwent ECD for non-reassured fetal heart rate status.Methods: This retrospective cohort study involved 426 mother-infant pairs over four years. We retrieved data from the medical records, including baseline characteristics, perioperative data, and neonatal outcomes. Using multivariable logistic regression analysis, adjusted odd ratios, and a 95% confidence interval, potential factors influencing S-D time and their impacts on neonatal outcomes were assessed. A p-value of less than 0.05 was considered statistically significant.Results: Factors independently associated with longer S-D time (> 8 minutes) were mothers who had previous CD (AOR 5.9: 95% CI 2.2-16.1), obese mothers (AOR 6.2: 95% CI 1.6-24.5), and the second stage of labor (AOR 5.3: 95% CI 2.4-11.7). Adverse neonatal outcomes, including a 5th minute Apgar score of less than 7, the need for NICU admission, and neonatal death, were significantly higher in the longer S-D time interval [47.7% vs. 8.9%; p-value 0.001], [21.9% vs. 9.1%; p-value 0.001], and [32% vs. 11.8%; p-value =0.004], respectively. Obese mothers and the second stage of labor, but not previous CD, adversely impact neonatal outcomes.Longer S-D times are significantly associated with adverse neonatal outcomes.Factors that prolong the time interval between skin incision and delivery may or may not necessarily be associated with adverse neonatal outcomes. Considering surgical techniques that shorten the incision-delivery time and preparation for advanced neonatal care for risky subjects would help reduce detrimental neonatal consequences.